Effects of HPV Pseudotype Virus in Cutting E6 Gene Selectively in SiHa Cells - Cheng, Yan-xiang; Chen, Gan-tao; Yang, Xiao; Wang, Yan-qing; Hong, Li (Current medical science, 2018)
Summary The objectives of this study were to investigate the effects of the CRISPR/Cas9 system mediated by the HPV pseudotype virus on SiHa cytobiology behavior by cutting the HPV16 E6 gene selectively and to explore the role of this system in the treatment of cervical cancer. After designing specific gRNA sequences targeting HPV16 E6, generating hCas9-EGFP and E6-gRNA-RFP plasmids, and preparing the pseudovirus of HPV16 carrying E6-gRNA and Cas9 plasmids, we determined the titer of the pseudotype virus using the TCID50 method. We obtained the pseudotype virus of HPV16 carrying E6-gRNA and Cas9 plasmids to transfect cervical cancer SiHa cells. Experimental subjects were divided into control group, empty virus group, E6-gRNA transfected group, Cas9 transfected group and Cas9+E6-gRNA transfected group. The molecular size of the cutting sequence was detected using the T7E1 enzyme digestion method and agarose gel electrophoresis, and the cleavage function of CRISPR/Cas9 on the E6 gene was determined at the same time. RT-PCR and Western blotting were performed to detect the mRNA and protein expression levels of E6 in all the groups; the Transwell cell migration assay was performed to detect the cell migration ability and metastasis in all groups. Heterotopic transplantation tumors were incorporated into mice and were used to investigate the effects of the CRISPR/Cas9 system mediated by the HPV pseudovirus on the tumorigenic ability of SiHa cells by selectively cutting HPV16 E6. The HPV16 pseudotype virus carrying E6-gRNA and Cas9 plasmids could successfully infect SiHa cells, and there were two cutting zones in the Cas9+E6-gRNA transfected group. However, the empty virus group, E6-gRNA transfected group and Cas9 transfected group had no corresponding zone. Compared with those in the control group, the empty virus group, E6-gRNA transfected group and Cas9 transfected group, the mRNA and protein expression levels of E6 in SiHa cells were downregulated in the Cas9+E6-gRNA transfected group ( P <0.01). In addition, the proliferation and migration abilities of SiHa cells were significantly inhibited ( P <0.01). There were no significant differences among the other groups. In contrast to the control group, the HPV pseudotype virus carrying E6-gRNA and Cas9 plasmids could significantly delay the growth of tumor cells of the ectopic tumor transplantation model ( P <0.01). The CRISPR/Cas9 system mediated by the HPV pseudotype virus to knockout E6 gene expression exhibited a clear inhibitory effect on the biological function of SiHa cells, which indicated that knocking out the E6 gene using the CRISPR/Cas9 system mediated by the HPV pseudotype virus had a potential effect of eliminating HPV infection and inhibiting the growth of HPV-related tumors. Taken together, these findings provide insight into a new treatment strategy for the prevention and treatment of hr-HPV infected disease, particularly in HPV-related tumors.